Quantificação de antimônio em garrafas de politereftalato de etileno (PET) brasileiras por fluorescência de raios-X e avaliação quimiométrica para verificar a presença de pet reciclado através do teor de ferro - Gustavo G. Shimamoto; Bianca Kazitoris; Luis F. R. de Lima; Nathassia D. de Abreu; Vitor T. Salvador; Maria Izabel M. S. Bueno; Eustáquio V. R. de Castro; Elói A. S. Filho; Wanderson Romão (Química Nova, 2011)
Antimony is a common catalyst in the synthesis of polyethylene terephthalate used for food-grade bottles manufacturing. However, antimony residues in final products are transferred to juices, soft drinks or water. The literature reports mentions of toxicity associated to antimony. In this work, a green, fast and direct method to quantify antimony, sulfur, iron and copper, in PET bottles by X-ray fluorescence spectrometry is presented. 2.4 to 11 mg Sb kg-1 were found in 20 samples analyzed. The coupling of the multielemental technique to chemometric treatment provided also the possibility to classify PET samples between bottle-grade PET/recycled PET blends by Fe content.